Multi-Spectroscopic and Molecular Simulation Approaches to Characterize the Intercalation Binding of 1-Naphthaleneacetic Acid With Calf Thymus DNA - Hu, Xing; Luo, Xiaoqiao; Zhou, Zhisheng; Wang, Rui; Hu, Yaqin; Zhang, Guimei; Zhang, Guowen (Frontiers in Toxicology, 2021)
1−Naphthaleneacetic acid (NAA), a broad-spectrum plant growth regulator, is widely used in agricultural production. Although NAA is a low toxic pesticide, its long-term large-scale use will affect the growth and development of aphids, and even affect the balance of human metabolism, which has certain damage to the human body. In this study, the interaction of NAA with calf thymus DNA (ctDNA) was investigated under simulated human physiological acidity (pH 7.4) using fluorescence, ultraviolet-visible absorption, and circular dichroism spectroscopy combined with viscosity measurements and molecular simulation techniques. The results demonstrated that the quenching of endogenous fluorescence of NAA by ctDNA was a mixed quenching process which mainly resulted from the formation of NAA−ctDNA complex. NAA mainly interacted with ctDNA through hydrophobic interaction, and the binding constant and quenching constant at room temperature (298 K) were 0.60 × 105 L mol−1 and 1.58 × 104 L mol−1, respectively. According to the analysis of melting point, KI measurements and viscosity of ctDNA, the binding mode of NAA with ctDNA was intercalation. The results were confirmed by molecular simulation, and it showed that NAA was enriched near the C−G base of ctDNA. The results of circular dichroism spectroscopy showed that the binding of NAA induced the transformation of the secondary structure of ctDNA from B-form to A-form. These researches will help to understand the hazardous of NAA to human body more comprehensively and concretely, so as to better guide the use of NAA in industry and agriculture.